Too Many Managers: The Strategic Use of Titles to Avoid Overtime Payments - Cohen, Lauren H; Gurun, Umit G; Ozel, N Bugra (Review of Financial Studies, 2026)
Abstract We find widespread evidence that firms avoid overtime payments by strategically assigning “managerial” titles. Exploiting the exemption threshold under the Fair Labor Standards Act (FLSA), we find managerial titles increase almost fivefold just above the overtime pay cutoff, including suspect listings, such as “Director of First Impressions” for a role equivalent to “Front-Desk Clerk.” Avoidance is higher when firms have more bargaining power and are financially constrained. It is also more common in occupations with volatile demand and unpredictable worker scheduling. Patterns align with litigation and Department of Labor enforcement. Firms avoid roughly 13.5% in compensation costs, hiring strategic “managers.”